Fad fibers incorporated a plant design - Aspa, Lornalie; Daguio, Purisima; Fernandez, Pilar (Quezon City College of Engineering, 1970)
This project is designed to determine the economic and technical feasibility of producing fibers from soybean protein. The attraction of soybean as a raw material for fiber lies in its high protein content. Economically, it is sound. The supply of soybeans is large and increasing yearly; the price is low and generally, stable. Soybean oil, which is fast becoming one of our most important vegetable oils, is recovered in the first step of the fiber production. Soybean fiber finds its main use as a suitable blend for cotton, wool, and spun rayon. In the Philippines, soybean fiber will find an attractive market in the textile industry. The manufacture of soybean fiber generally consists in: extracting the oil from crushed soybeans and recovering the meal, extracting the protein from the meal, and finally processing the extracted protein (aging, spinning, hardening, drying) to fibers.
Typescript.
Plant design.
Keywords: Factories -- Design and construction; Plant fibers